If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8 + -2(2x) + (16 + 3) = -4x + -3 + 2x Remove parenthesis around (2x) 9x + -8 + -2 * 2x + (16 + 3) = -4x + -3 + 2x Multiply -2 * 2 9x + -8 + -4x + (16 + 3) = -4x + -3 + 2x Combine like terms: 16 + 3 = 19 9x + -8 + -4x + (19) = -4x + -3 + 2x 9x + -8 + -4x + 19 = -4x + -3 + 2x Reorder the terms: -8 + 19 + 9x + -4x = -4x + -3 + 2x Combine like terms: -8 + 19 = 11 11 + 9x + -4x = -4x + -3 + 2x Combine like terms: 9x + -4x = 5x 11 + 5x = -4x + -3 + 2x Reorder the terms: 11 + 5x = -3 + -4x + 2x Combine like terms: -4x + 2x = -2x 11 + 5x = -3 + -2x Solving 11 + 5x = -3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 11 + 5x + 2x = -3 + -2x + 2x Combine like terms: 5x + 2x = 7x 11 + 7x = -3 + -2x + 2x Combine like terms: -2x + 2x = 0 11 + 7x = -3 + 0 11 + 7x = -3 Add '-11' to each side of the equation. 11 + -11 + 7x = -3 + -11 Combine like terms: 11 + -11 = 0 0 + 7x = -3 + -11 7x = -3 + -11 Combine like terms: -3 + -11 = -14 7x = -14 Divide each side by '7'. x = -2 Simplifying x = -2
| 5x+2-7x+8= | | 19x^2+24x+9=0 | | (5/4x)+(1/8x)=(11/8)+x | | 4(-5x+6x)=-28 | | 229=2x-12x | | 3(4-2n)=-6(n+8) | | y=7x+12 | | 3+8n=-7+7+8n+3 | | y=7+12 | | -3k-39=8(7x-5)+1 | | 12(2x-2)=4(6x+8) | | y/3+4-2 | | 7=3x+4x | | 9+10m-7=7m+66-5m | | 81=8a-1a | | 4x+19=x+7 | | (2/3)x+7=8x-6 | | 6/270 | | 2a=48 | | (-6+1)*4+5/5+2 | | 10g=30 | | 9d+4=4d-13 | | 3ln(2x+3)=9 | | Y+2x=-3 | | 3d-3=-15 | | 2w-3=9 | | 4/3x-7=-11 | | x^2+(-3x)=0 | | 6c-21=9 | | (2x+2)(x)=220 | | 2x+1x+3y+1y=12+51 | | -5x+3(2x-4)=x-1/4(6-15x) |